The influence mechanism of relative deprivation on prosocial behavior of migrant children: based on the mediating effect of self-esteem and the moderating effect of social support - Zhang, Xueqi; Yan, Fengjuan; Meng, Lin (Frontiers in Psychology, 2025)
Prosocial behavior refers to a series of behaviors that are beneficial to others and social harmony, such as humility, assistance, cooperation and sharing, which are important aspects of adolescent social ability development. With the acceleration of urbanization in China, the scale of the floating population continues to expand. The structural change of “family mobility” makes migrant children become a huge group in urban society that cannot be ignored. Promoting the social integration and urban inclusion of migrant children has become a critical interdisciplinary research focus. This study examines the impact of relative deprivation on prosocial behavior among migrant children, specifically investigating the mediating role of self-esteem in this relationship and the moderating role of social support between self-esteem and prosocial behavior. Using multi-stage clustered PPS (Probability Proportional to Size) sampling, data were collected from 1,428 migrant adolescents across 12 schools in central Jinan, Shandong Province. Prosocial behavior, relative deprivation, self-esteem, and perceived social support were assessed via standardized scales. The results indicate a significant negative effect of relative deprivation on prosocial behavior among migrant children. This inhibition is partially mediated by self-esteem, while social support positively moderates the relationship between self-esteem and prosocial behavior. The findings suggest that enhancing prosocial behavior among migrant children requires proactive emotional interventions. These interventions should aim to boost self-perception and self-identity, elevate self-esteem, reduce feelings of relative deprivation, and address educational challenges. Social networks-supported multi-pronged approaches are needed to foster social integration.